Supreme Court Confirmation Hearings in the U.S. Senate : Reconsidering the Charade - Farganis, Dion; Wedeking, Justin (Book collections on Project MUSE., 2014)
Critics claim that Supreme Court nominees have become more evasive in recent decades and that Senate confirmation hearings lack real substance. Conducting a line-by-line analysis of the confirmation hearing of every nominee since 1955-an original dataset of nearly 11,000 questions and answers from testimony before the Senate Judiciary Committee-Dion Farganis and Justin Wedeking discover that nominees are far more forthcoming than generally assumed. Applying an original scoring system to assess each nominee's testimony based on the same criteria, they show that some of the earliest nominees wer.